MANAGEMENT OF BROAD MITE, POLYPHAGOTARSONEMUS LATUS (BANKS) USING BIOLOGICAL CONTROL AGENTS AND THEIR IMPACT ON THE QUANTITATIVE AND QUALITATIVE PARAMETERS OF MULBERRY - B. S. Ramesha; SHREEROOPA (The Journal of Research ANGRAU, 2025)
The study was conducted during April 2022 to February 2024. The broad mite, Polyphagotarsonemus latus occurrence alters the plant growth,leaf yield and quality parameters  of mulberry. The study revealed that the damages of broad mite influences greatly on quality and nutritional content of mulberry leaf. Significant differences were observed on plant growth, leaf  yield and nutritional content of mulberry leaves. All the growth parameters were highest when the  broad mite occurrence was managed by using treatment Pongamia oil @ 3 ml/l i.e., Number of  shoots per plant (15.89), number of leaves per shoot (16.61), plant height (183.27cm), number of  leaves per plant(168.27), leaf yield per plant (882.07 g). On the other hand the biochemical  constituents of the mulberry leaves were also increased in the treatment imposed plots compared  untreated control. The treatment Pongamia oil @ 3 ml/l recorded highest amount crude protein  (21.46 mg/g), chlorophyll-A (1.535 mg/ml) and total chlorophyll content (1.850 mg/ml) of mulberry leaves. Overall the study revealed that the biological agents including entomopathogenic fungi  (H. thompsonii(26.46%) & L. lecanii(26.12%)) botanicals (Pongamia (32.83)& Neem oil (32.28%)) and predator (S. punctillum(21.09%) & N. indicus (24.09%)) could be used successfully to manage  the broad mite occurrence in mulberry to enhance the leaf yield and quality